Exit, Voice, and Sabotage: Public Service Motivation and Guerrilla Bureaucracy in Times of Unprincipled Political Principals. (24th July 2021) - Schuster, Christian; Mikkelsen, Kim Sass; Correa, Izabela; Meyer-Sahling, Jan-Hinrik
Abstract: Democratic backsliding has multiplied "unprincipled" political principals: governments with weak commitment to the public interest. Why do some bureaucrats engage in voice and guerrilla sabotage to thwart policies against the public interest under "unprincipled principals, " yet others do not? Despite its centrality in contemporary governance, this conundrum has not seen quantitative research. We address this gap with survey evidence from 1, 700 Brazilian public servants during the Temer Presidency, widely perceived to lack democratic legitimacy and integrity. We focus on one key explanator: public service motivation (PSM). We argue that bureaucrats with greater PSM are more likely to engage in voice and sabotage of "unprincipled policies, " and exit to avoid implementing "unprincipled policies." Structural equation models support these hypotheses. Public service-motivated bureaucracies are thus short-run stalwarts against "unprincipled" political principals. Over time, they look to depart, however, leaving "unprincipled" principals a freer hand to pursue policies against the public interest.